Contributing to regional development through project selection - Bertrand Rossert (EIB Papers, 2000)
The EIB finances a large number of projects in support of EU policies including social and economic cohesion, that is to reduce regional disparities in income. Since 1995, the EIB Evaluation Department has looked at over 100 projects where the Bank has been involved, normally along the lines of a particular theme (e.g. impact of the Banks projects in a specific sector or region). Inevitably, the information gathered is patchy because very few statistical series exist at a sufficient level of disaggregation to be used for ex-post project analysis. As any case-study work, their main value is to tell us whether a problem exists or not, rather than to assess the exact magnitude of the problem. A series of evaluations has been structured around a regional development theme. In the most recent study of 17 projects, 14 of them had some positive impact on regional development and in over half of these cases, the impact was a strong one. Can the Bank improve on this, or at least maintain the same record? Clearly, this requires an understanding of the type of projects that contribute most to regional development. The purpose of this paper is to discuss what has been learned so far on this subject.
Keywords: 330; Entwicklungsprojekt; Theorie; EU-Staaten; Regionalpolitik